Efikasi Diri: Mediator Pendidikan Kewirausahaan dan Kecerdasan Adversitas Terhadap Intensi Berwirausaha Mahasiswa - Rosnaeni Arsyad; Kasman, Risqah Amaliah (Almeera Education, 2024)
High unemployment is a complex problem that requires multidimensional solutions. One potential solution is to encourage entrepreneurial spirit among students. By creating new jobs, students can not only improve their welfare but also make a positive contribution to society. The purpose of this study was to assess the impact of entrepreneurship education and adversity intelligence on entrepreneurial intention, with self-efficacy as a mediating variable. This study used a questionnaire compiled based on the indicators of each variable as an instrument and distributed through Google Forms. A total of 210 participants were obtained from sampling through a non-probability sampling method with a purposive sampling technique. The data obtained were then processed using SmartPLS version 4.0. The results showed that there was a positive and significant effect of entrepreneurship education and adversity intelligence on self-efficacy. In addition, entrepreneurship education and self-efficacy also had a positive and significant effect on entrepreneurial intention. Adversity intelligence was shown to have a positive but not significant effect on entrepreneurial intention.